2011
DOI: 10.1055/s-0031-1300084
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cetylpyridinium Chloride Used as Oropharyngeal Antiseptic

Abstract: Cetylpyridinium chloride, (CPC, CAS 123-03-5) as active ingredient of antiseptic oral mouthrinses has a broad antimicrobial spectrum with a rapid bactericidal effect on gram-positive pathogens and a fungicide effect on yeasts in particular. There are gaps in its effectiveness against gram-negative pathogens and mycobacteria. Application of CPC at a concentration of 0.05% as a mouthrinse results in an immediate reduction in bacterial counts of 2.0 to 2.5 log steps (which is adequate to > 99%). This reverts to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 29 publications
0
44
0
11
Order By: Relevance
“…The combination of CPC with chlorhexidine and zinc lactate brings the highest reduction of both anaerobic and aerobic microorganisms, thus preventing the occurrence of bad breath (11). The effectiveness of CPC against oropharingeal candidiase has also been confi rmed (12).…”
Section: Introductionmentioning
confidence: 97%
“…The combination of CPC with chlorhexidine and zinc lactate brings the highest reduction of both anaerobic and aerobic microorganisms, thus preventing the occurrence of bad breath (11). The effectiveness of CPC against oropharingeal candidiase has also been confi rmed (12).…”
Section: Introductionmentioning
confidence: 97%
“…As a surface-active agent, it has a broad antimicrobial spectrum and is particularly effective at killing Gram-positive pathogens and yeasts. 12) CPC has been shown to significantly improve plaque-associated gingivitis, which can precede periodontitis. 19) Alveolar bone resorption as a result of enhanced osteoclast activity is commonly observed in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is an antiseptic agent with a broad antimicrobial spectrum and has rapid bactericidal effects on Gram-positive pathogens and fungicidal effects on yeasts. 12) It is assumed that it kills bacteria by disturbing membrane function, thereby causing leakage of cytoplasmic material and ultimately the collapse of the intracellular equilibrium. 12,13) Research has demonstrated that CPC is effective in preventing gingival inflammation, thereby helping to prevent periodontitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of laboratory studies are available in the literature that report the broad spectrum activity of CPC on a range of organisms, including bacteria and yeast found in dental plaque [3][4][5]. a moderate plaque inhibition was obtained when CPC was applied twice daily as a mouthwash [6].…”
mentioning
confidence: 99%